2001
DOI: 10.1002/jmv.2055.abs
|View full text |Cite
|
Sign up to set email alerts
|

Resistance profile and cross‐resistance of HIV‐1 among patients failing a non‐nucleoside reverse transcriptase inhibitor‐containing regimen

Abstract: The objectives were to determine the resistance profile and the rate of cross-resistance in HIV-1 infected patients failing an efavirenz or a nevirapine or a nevirapine then efavirenz containing regimens, and to investigate if zidovudine and more generally thymidine analog nucleosides lead to a particular genotypic pattern in nevirapine failing patients. A study was conducted in 104 patients with virological rebound to a non-nucleoside reverse transcriptase inhibitors (NNRTI) regimen (efavirenz n = 39, nevirap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 12 publications
1
19
0
Order By: Relevance
“…Resistance to NNRTI was found in 6% of cases, consistently with extensive use and with high likelihood of resistance development to this class [Delaugerre et al, 2001]. A survey conducted over the period 1996-2002 among seroconverters in the Italian ICONA cohort reported a prevalence of mutations in the RT region of 15.2%, but only 1 out of 112 isolates carried mutations related to NNRTI resistance [Violin et al, 2004b].…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to NNRTI was found in 6% of cases, consistently with extensive use and with high likelihood of resistance development to this class [Delaugerre et al, 2001]. A survey conducted over the period 1996-2002 among seroconverters in the Italian ICONA cohort reported a prevalence of mutations in the RT region of 15.2%, but only 1 out of 112 isolates carried mutations related to NNRTI resistance [Violin et al, 2004b].…”
Section: Discussionmentioning
confidence: 99%
“…Tel: 1 41 44 255 34 50; fax: 1 41 44 255 32 91; e-mail: huldrych.guenthard@usz.ch [1,2]. Because of the overlapping resistance profiles of currently approved NNRTI drugs, cross-resistance can emerge rapidly, which excludes future use of this drug class [3][4][5]. Recently, the situation has changed with the introduction of the diarylpyrimidine derivative etravirine (ETV), a novel, next-generation NNRTI [6].…”
Section: Introductionmentioning
confidence: 99%
“…78 Oteromycin exhibited much reduced inhibition compared to the other three structural homologs. 80 Integrasone [63], 81 a dihydroxy bicyclic epoxy lactone polyketide fungal metabolite, isolated by same group from an unidentified mycelium, which moderately inhibited the strand transfer reaction of HIV-1 integrase with an IC 50 value of 41 mM. The aliphatic chain may play a significant role in the activity, as was observed in the case of integric acid.…”
Section: Inhibitors Of Hivmentioning
confidence: 92%
“…Both clinical and in vitro studies have shown that E138K is a resistant mutation to ETR and RPV, which were approved by the FDA in 2008 and 2012, respectively. 63,64 Therefore, there remains a strong demand for the development of new NNRTIs that can effectively inhibit NNRTI-resistant viruses.…”
Section: Inhibitors Of Hivmentioning
confidence: 99%